HDAC3 inhibition mitigates acute kidney injury by alleviating RIPK1-mediated programmed necrosis - Xie, Manman; Hou, Rui; Shan, Runrun; Cheng, Xinyu; Wu, Pengcheng; Luo, Xiufeng; Wei, Yangyang; Gao, Li; Liu, Xiaoying; Chen, Qi (Frontiers in Pharmacology, 2025)
Acute kidney injury (AKI) refers to clinical syndromes culminating in rapidly reduced renal function associated with inflammation and the demise of renal tubular epithelial cells. Current research aims to develop strategies which prevent tubular cell death. Here, based on the involvement of histone deacetylases (HDACs) in renal physiology and their established role in renal fibrosis, we investigated the mechanistic contributions of HDACs using a mouse model together with in vitro studies employing human renal epithelial cells. We found HDAC3 expression was upregulated in mouse renal tubules after ischemia/reperfusion and cisplatin treatment. Instructively, treatment with the HDAC3 selective inhibitor RGFP966 exerted potent protective effects, attenuates acute kidney injury in both in vivo and in vitro models. Moreover, RGFP966 was found to reduce inflammation and injury caused by cisplatin and hypoxia-reoxygenation in HK2 cells with transcriptome sequencing revealing that RGFP966 significantly inhibited the upregulation of the necroptosis initiator, RIPK1. Cellular thermal displacement assay and molecular docking demonstrated the physical binding of RGFP966 to HDCA3. In addition, RIPK1 knockdown cell assay signified that RGFP966 targeted RIPK1 and inhibited RIPK1 kinase activity. In summary, these findings established the efficacy of the HDAC3 inhibitor RGFP966 in treating AKI.